Legal violence and the limits of the law - Nichols, Joshua Ben David; Swiffen, Amy (A GlassHouse book, 2018)
It's not just a good idea, it's the law : rationality, force, and changing minds / Mark Kingwell -- Cruel and thus not unusual : Jacques Derrida's seminar on the death penalty / Michael Naas -- The violent rhetoric of accusation : Cicero and the Marcus Ameleus Scaurus case / G. Pavlich -- The colonialism of incarceration / Robert Nichols -- Ran away from her master : a negroe girl named Thursday: examining evidence of punishment, isolation, and trauma in Nova Scotia and Quebec fugitive slave advertisements / Charmaine Nelson -- The work of death : massacre and retribution in Southampton County, Virginia, August 1831 / Christopher Tomlins -- Civilising missions and humanitarian interventions : into the laws and territories of first nations / Irene Watson -- The rhetoric of abolition : continuity and change in the struggle against America's death penalty, 1900-2010 / Austin Sarat, Robert Kermes, Adelyn Curran, Margaret Kiley, Keshav Pant -- Too wicked to die : the enduring legacy of humane reforms to solitary confinement / Kelly Struthers Munford, Kelly Hannah-Moffat, and Alex Hunter -- Nonviolent communion versus medieval ships of fools : engaged-citizenry alternatives to Europe's war on refugees / Pablo Ouziel